Dividend Policy Trend: A Comprehensive Study on the Listed Industrial Sector of Bangladesh - Islam, Mohammad Shahidul Shahidul; Atm, Adnan (Buhalterinės apskaitos teorija ir praktika, 2019)
The financial decision is rotated around the dividend decision. The objective is to identify the dividend pattern and the management’ views of dividend policy for revealing the present scenario of dividend practices in the capital market of Bangladesh. The parametric test, non-parametric test and percentile are used for inferring the result. In the manufacturing sector, the miscellaneous sector provides the highest payout. The DPS, EPS, MPS of the large size firm is better than small and medium size firms. The payout of the older firms is more than the newly listed firms. The highest payouts are in medium leveraged firm, low risk’s firm, medium PE ratio’s firm. The survey results reveal that the both shareholders and companies prefer the cash dividend most because of majority shareholders’ expectation. The most of the companies pay cash dividend with stable payout. The majority companies follow increasing trend in dividend payment but there is no satisfactory research to justify the investors’ preference. The capital market related stakeholders should follow these findings.
Keywords: Dividend; EPS; Signaling Theory; MM model